Kajian Kelayakan Ekonomi Proyek Dan Tarif Air Bersih Berdasarkan Metode Contingen Valuation Kota Dumai - Ferry Anggriawan; Ari Sandhyavitri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
The main purpose of this study is to determine the appropriate water rate based on the willingness to pay  Dumai city . This is due to the growing need for clean water in the city of Dumai  each year while the supply of clean water provided by the government is very limited. The method used in this research is  contingent valuation by  using the Statistical package for the social sciences (SPSS) to estimate the water rates in the city of Dumai. Of the water rates will be in the analysis of the Net Present Value, Benefit cost ratio, break-even point and the internal rate of return clean water projects Dumai. Addressing the needs of the water carried phasing with 4 scenarios for each of the water supply capacity starts from 80 Liter / sec in the year 2013-2014 and 160 liters / sec in the year 2016-2032. Results of analysis gives an overview of the feasibility of water  rates  projects in the city dumai with water service coverage includes 4  Dumai  of  District. East Dumai, Dumai Dumai City and South. Keywords: water rates, project feasibility, water clean, contingent valuation